2015
DOI: 10.1371/journal.pone.0143038
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Structure and Charge as a Key to Allosteric Modulation of Human 20S Proteasome by the Basic Fragment of HIV-1 Tat Protein

Abstract: The proteasome is a giant protease responsible for degradation of the majority of cytosolic proteins. Competitive inhibitors of the proteasome are used against aggressive blood cancers. However, broadening the use of proteasome-targeting drugs requires new mechanistic approaches to the enzyme’s inhibition. In our previous studies we described Tat1 peptide, an allosteric inhibitor of the proteasome derived from a fragment of the basic domain of HIV-Tat1 protein. Here, we attempted to dissect the structural dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…This goal was accomplished by generating structural derivatives of the TAT1 peptide that contained turn-inducing moieties and the preserved key basic residues (Table 1). Our previous structural studies of the TAT1 peptide suggested a strong preference toward formation of two β-like turns in positions 4,5 and 8,9 [22,24] ( Figure 1B, C). Substitutions of residues in TAT1 with alanines (Ala-walking) confirmed the significance of the putative turn regions for core proteasome activation ( Figure 2).…”
Section: Design Of Tat Peptidesmentioning
confidence: 69%
See 4 more Smart Citations
“…This goal was accomplished by generating structural derivatives of the TAT1 peptide that contained turn-inducing moieties and the preserved key basic residues (Table 1). Our previous structural studies of the TAT1 peptide suggested a strong preference toward formation of two β-like turns in positions 4,5 and 8,9 [22,24] ( Figure 1B, C). Substitutions of residues in TAT1 with alanines (Ala-walking) confirmed the significance of the putative turn regions for core proteasome activation ( Figure 2).…”
Section: Design Of Tat Peptidesmentioning
confidence: 69%
“…The whole Tat protein not only inhibits the core proteasome but also competes with the PA28/REG activator [21]. As mentioned above, we found before that TAT1 inhibits the artificially activated 20S core in vitro, but noted that it can activate the naturally latent core [22][23][24]. The goal of our design was to enhance the proteasome activation and improve the peptide's stability while preserving BBB penetrance.…”
Section: Design Of Tat Peptidesmentioning
confidence: 77%
See 3 more Smart Citations